Winter pruning timing, development and quality of Cabernet Sauvignon in Southern Brazil - Aloy, Keila; Gobi, Samuel Francisco; Martins, Hyoran Caius Genindo Barreto; Jacobs, Suziane Antes; Eckhardt, Daniel Pazzini; Brighenti, Alberto Fontanella; Schumacher, Rafael Lizandro; Costa, Vagner Brasil (Comunicata Scientiae, 2025)
The objective of this study was to evaluate the influence of winter pruning timing on phenology, productivity, and quality of Cabernet Sauvignon grapes and wines in 2022/2023 production cycle. The experimental design was randomized blocks, with 3 replications, each experimental unit consisted of 5 plants. The treatments involved four pruning timings (end of May, June, July and August). Phenology assessments were beginning and end of bud break, flowering, maturation and percentage of bud break. Production was evaluated by the number of clusters per plant, weight and size of clusters, productivity per plant and per hectare. The analyzes of must were pH, total acidity and soluble solids (°Brix). In wine, pH, total acidity, sugars, alcohol, volatile acidity and color were analyzed. In the end a wine sensory analysis was carried out. The results showed that the bud break of plants pruned early, in May, occurred at the same time as plants pruned in June and July. Early pruning resulted in lower productivity. The grape must from plants pruned late, in August, showed higher total acidity and lower values ​​of soluble solids and sugars. Early pruning did not change the duration of the cultivar's phenological subperiods, nor did it bring forward the harvest in relation to the control. The different pruning times influenced productivity more than the composition of grapes and wines, indicating that it is possible to extend the pruning period.